Postales de la violencia. La representación de la favela en "El sol en la cabeza", de Geovani Martins - Leonardo-Loayza, Richard (2022)
This article aims at analyzing the way Geovani Martins' storybook El sol en la cabeza represents the world of favelas, as well as to reflect on the relationship between such geocultural space and violence. Our main hypothesis is that Martins' representation goes beyond what has traditionally been reported on favelas, namely a dangerous place, marked by criminality, and a generator of violence. It is not that the book denies these attributes, but rather that it reinterprets them, thus demonstrating that reality is more complex than what is propagated in the media. To carry out the analysis, we will focus on three stories from El sol en la cabeza: "La historia de Periquito y Cara de Mono", "La firma" and "El Ciego".